2016
DOI: 10.1016/j.bbmt.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Survival Impact of Early Post-Transplant Toxicities in Pediatric and Adolescent Patients Undergoing Allogeneic Hematopoietic Cell Transplantation for Malignant and Nonmalignant Diseases: Recognizing Risks and Optimizing Outcomes

Abstract: In pediatric and adolescent patients undergoing allogeneic hematopoietic cell transplantation, treatment-related toxicities remain a clinical challenge. A paucity of data investigates the risks for and survival impact of treatment-related toxicities in this population. Here the authors assess the relative toxicity of myeloablative, reduced-toxicity, and reduced-intensity conditioning regimens; identify patient-related predictors of post-transplant toxicities; and investigate the impact of early post-transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In HSCT, the phase of hematopoietic cell infusion (HCI) is a time when acute regimen-related toxicities often occur. 2,3 In addition, HCI itself can lead to adverse events (AEs), such as flushing, nausea and vomiting, malodor, hypotension, hypertension, allergic reactions, arrhythmia, encephalopathy, and respiratory distress. [4][5][6][7][8][9][10] AEs associated with blood transfusion, which is usually component-based therapy, have been widely and routinely surveyed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HSCT, the phase of hematopoietic cell infusion (HCI) is a time when acute regimen-related toxicities often occur. 2,3 In addition, HCI itself can lead to adverse events (AEs), such as flushing, nausea and vomiting, malodor, hypotension, hypertension, allergic reactions, arrhythmia, encephalopathy, and respiratory distress. [4][5][6][7][8][9][10] AEs associated with blood transfusion, which is usually component-based therapy, have been widely and routinely surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Kazuhiko Ikeda , 1,2 Hitoshi Ohto, 1,2 Minami Yamada-Fujiwara, 1,3 Yoshiki Okuyama, 1,4 Shin-ichiro Fujiwara , 1,5 Kazuo Muroi, 1,6 Takehiko Mori, 7 Kinuyo Kasama, 8 Heiwa Kanamori, 1,9 Tohru Iseki, 1,10 Tokiko Nagamura-Inoue, 1,11 Kazuaki Kameda, 12 Junya Kanda, 13 Kazuhiro Nagai, 14 Nobuharu Fujii, 15 Takashi Ashida, 16 Asao Hirose, 17 Tsutomu Takahashi, 18 Keiji Minakawa, 2 and Ryuji Tanosaki 1 BACKGROUND: Hematopoietic cell infusion-related adverse events (HCI-AEs) in hematopoietic stem cell transplantations (HSCTs) have been largely attributed to toxicity of dimethyl sulfoxide (DMSO) for cryopreservation, but HSC products also contain various cells and plasma components. Our recent prospective study of 1125 HSCT recipients revealed the highest overall HCI-AE rate in bone marrow transplantation (BMT) using fresh/noncryopreserved products, although products of peripheral blood stem cell transplantation and cord blood transplantation (CBT) are generally cryopreserved with DMSO containing smaller plasma volumes.…”
mentioning
confidence: 99%
“…Conditioning regimens were disease‐specific and protocol‐driven in accordance with institutional and cooperative group studies. Details of conditioning regimens used for both autoHCT and alloHCT have been previously published by our group . In brief, myeloablative conditioning regimen consisted of either TBI [12 Gray] + 1‐2 high‐dose alkylators or busulfan (12.8‐16 mg/kg) + 1 high‐dose alkylators .…”
Section: Methodsmentioning
confidence: 99%
“…RIC regimens contained busulfan (6.4‐8 mg/kg) or melphalan (140 mg/m 2 ) + fludarabine. Serotherapy consisted of alemtuzumab (54 mg/m 2 ) or ATG (8 mg/kg) …”
Section: Methodsmentioning
confidence: 99%
“…The results an analysis by Burroughs et al of patients with non-malignant diseases indicate that RTC conditioning is effective and improves survival due to its lower toxicity [25]. However, Al Mulla et al showed that reduced-toxicity conditioning was not significantly less toxic than myeloablative in pediatric and adolescent patients undergoing allogeneic HCT [26]. In our study, pediatric TRM score had no effect on TRM and OS, probably because the type of non-malignant disease was not included in the TRM stratification, and according to our analysis, the underlying disease affected survival after HCT.…”
Section: Discussionmentioning
confidence: 99%